Gait variability across neurodegenerative and cognitive disorders: Results from the Canadian Consortium of Neurodegeneration in Aging (CCNA) and the Gait and Brain Study. Issue 8 (16th February 2021) - Pieruccini‐Faria, Frederico; Black, Sandra E.; Masellis, Mario; Smith, Eric E.; Almeida, Quincy J.; Li, Karen Z. H.; Bherer, Louis; Camicioli, Richard; Montero‐Odasso, Manuel
Abstract: Introduction: Gait impairment is common in neurodegenerative disorders. Specifically, gait variability—the stride‐to‐stride fluctuations in distance and time—has been associated with neurodegeneration and cognitive impairment. However, quantitative comparisons of gait impairments across the cognitive spectrum of dementias have not been systematically investigated. Methods: Older adults (N = 500) with subjective cognitive impairment, Parkinson disease (PD), mild cognitive impairment (MCI), PD‐MCI, Alzheimer's disease (AD), PD‐dementia, Lewy body dementia, and frontotemporal dementia, as well cognitive normal controls, who were assessed for their gait and cognitive performance. Results: Factor analyses grouped 11 quantitative gait parameters and identified four independent gait domains: rhythm, pace, variability, and postural control, for group comparisons and classification analysis. Among these domains, only high gait variability was associated with lower cognitive performance and accurately discriminated AD from other neurodegenerative and cognitive conditions. Discussion: Our findings indicate that high gait variability is a marker of cognitive‐cortical dysfunction, which can help to identify Alzheimer's disease dementia.